Shear behaviour of novel enhanced C-channel connectors in steel-concrete-steel sandwich composite structures. (March 2020) - Yan, Jia-Bao; Hu, Huitao; Wang, Tao
Abstract: This paper firstly reported a novel type of enhanced C-channel connectors (ECs) for steel-concrete-steel sandwich structures by the first author. The novel EC connectors were achieved through connecting the free end of C-channel outside of the specimen using bolts or blind bolts. A push-out testing program, consisting of 16 specimens, was then carried out to study shear behaviour of novel ECs. This experimental program studied the influences of strength of concrete core, length, height and layout of C-channels on shear behaviour of ECs. The test results showed that the ECs exhibited successive failure of bolts and C-channel connectors, and confirmed that ECs improved the shear behaviour of C-channel connectors in terms of ultimate shear resistance. Influences of the studied parameters on shear behaviour of ECs were studied and analysed. Including the experimental investigations, new analytical models were developed to predict ultimate shear resistance and shear versus slip law of ECs. Validations against the reported 16 push-out results confirmed that these developed analytical models predicted well ultimate shear resistance and shear-slip behaviour of novel ECs. Highlights: Novel enhanced C-channel (EC) connectors are proposed for sandwich composite walls. Shear behavior of novel EC connectors is studied by push-out tests. Parameters influencing shear behavior of EC connectors are studied and revealed. New theoretical models predict well ultimate shear resistance of EC connectors. New constitutive model predicts well shear-slip behavior of novel EC connectors.